Evaluasi Pelaksanaan Pelatihan Pengawas Benih dan Bibit Tanaman Hutan di Badan Pengembangan Sumber Daya Manusia Provinsi Jawa Timur - Daisy La Rosa Anggraini; Dian Arlupi Utami (Perspektif Administrasi Publik dan hukum, 2026)
This study aims to describe the evaluation of the Forest Seed and Seedling Supervisor Training in East Java Province using the four levels of the Kirkpatrick Evaluation Model. The method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation, and data analysis carried out through three stages: data reduction, data presentation, and conclusion drawing. The results show that at the reaction level, participants were satisfied with the materials and facilities but less satisfied with the instructors, time, and training location. The learning level showed an increase in participants' knowledge, reflected in high learning motivation as well as differences between pre-test and post-test scores. At the behaviour level, changes in behaviour were found, such as in communication and time management. Meanwhile, the result level showed improvements in participants' performance quality, both individually and in teamwork. This research recommends improvements in schedule planning, location selection, and instructor selection based on pedagogical competence, maintaining the relevance of materials and calibrating test instruments, as well as the need for post-training monitoring and evaluation of behavioural changes and performance impacts among participants.